Protoplasts Fusion of phalaenopsis and dendrobium = Fusi protoplas phalaenopsis dan dendrodium - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1991)
Protoplasts of Phalaenopsis and Dendrobium were isolated enzymatically. The protoplasts of Phalaenopsis are easily distinguished from the protoplasts of Dendrobium because they were purple in colour, and after enzymatic digestion the chloroplast were in cluster at a certain site of the protoplast. The fusion of both protoplast were done using various concentration of Polyethylene Glycol (PEG) and osmoliticum stabilizer. The first fusion occured 5 minutes after both protoplasts were mixed in 35 % of PEG with 0,3 M glucose and 50 mM CaCI2 while other than 35 % were not effective.